Thin Slice of Life - Arceneaux, Miles (Book collections on Project MUSE., 2013)
"Charlie Sweetwater returns to his hometown to visit his brother but arrives to find he is a no-show: The Coast Guard has discovered Johnny's shrimp boat drifting abandoned in the Gulf. Is it "death by misadventure" as the authorities presume, or something more sinister?"--Amazon.com.